S17. MAPPING OF WHOLE BRAIN MYO-INOSITOL LEVELS IDENTIFIES PREFRONTAL REDUCTIONS IN DEPRESSION. (9th April 2019) - Chiappelli, Josh; Rowland, Laura; Chen, Shuo; Wijtenburg, Andrea; Ryan, Meghann; Chen, Hongji; Bruce, Heather; Kochunov, Peter; Hong, Elliot
Abstract: Background: Abnormal cerebral levels of myo-inositol, a molecule involved in membrane phospholipid synthesis and regulation of intracellular processes, may be a biomarker for depression, including experience of depression within schizophrenia spectrum disorders. However, studies to date have resulted in mixed findings, in part due to limitations in comprehensive assessment of myo-inositol levels in different regions of the brain. Methods: We aimed to determine the regional pattern of myo-inositol changes in cortical gray matter in depression by using echo-planar spectroscopic imaging (EPSI) at 3T in a sample of 193 individuals from the Amish and Mennonite communities, of whom 59 had a current or past history of unipolar depression. The relationship of myo-inositol levels to depression was examined from a categorical approach (using diagnosis of unipolar depressive disorder) as well as a dimensional approach (measuring symptoms of depression using the Maryland Trait and State Depression scales). Regression models covarying for age, sex, and accounting for the high correlation of brain metabolites between regions were used to examine these relationships, with false discovery rate used to control for multiple comparisons. Results: Myo-inositol levels were lower in individuals with a history of depression compared to controls in 4 regions of the frontal and parietal cortex. Using a dimensional approach, myo-inositol levels were inversely correlated with trait depression (frequency of symptoms experienced over course of life) in 19 regions, primarily in frontal, limbic, and subcortical regions; however, myo-inositol was not strongly related to state depressive symptoms. Furthermore, lower myo-inositol was related to greater experience of stressful life events in 14 regions, largely overlapping with the regions associated with trait depression. Discussion: These results indicate that decreased myo-inositol levels specifically in frontal regions may be a biomarker for depression. The finding of a relationship between stressful life events and myo-inositol levels may have implications for further study of the trans-diagnostic mechanisms of stress related psychopathology.